Experimental investigation of course stability on a barge during damaged conditions - Suandar Baso (SINERGI, 2022)
The paper presents an experimental investigation of course stability on the barge due to the damage conditions of one or more adjacent void tanks. The effects of various towline lengths and load conditions on the course stability of the barge were taken into account and incorporated with trim and heel conditions. The sway motion, defined as the towline's motion, was captured using the camera, and the yaw motion was measured using the Euler compass. The investigation results revealed that increased towline lengths, flooding locations, and load conditions affect the barge's course stability. The smallest value is the increased sway and yaw amplitudes affected by the flooded condition of one or adjacent two void tanks on the amidship part. The overall sway amplitude on the port side or starboard side increases significantly high, affected by towline length from 1L to 1.5L. Also, the overall yaw amplitude on the port side or starboard side increases significantly high, affected by towline length from 1.5L to 2L. The difference in the increased sway amplitude based on the flooding locations between stern, amidship, and bow parts is less than 10% on the port side and 2% on the starboard side. The difference in the increased yaw amplitude is less than 5% on the port side and 5% on the starboard side. The number of longitudinal bulkheads on the port side and starboard side must be considered for the reduction of the oscillation of the water mass inside the tank to reduce the degradation of the course stability.